Psychotherapists' attitudes to intimate and informal behaviour towards clients. Issue 11 (18th August 2021) - Vesentini, Lara; Van Overmeire, Roel; Matthys, Frieda; De Wachter, Dirk; Van Puyenbroeck, Hubert; Bilsen, Johan
Abstract: Background: To avoid harming or exploiting a client, sexual and non-sexual dual relationship is generally considered as unacceptable in the psychotherapeutic relationship. However, little is known about what therapists themselves constitute as (un)acceptable intimate and informal behaviour (IIB). Methods: A survey among psychotherapists in Flanders (Belgium) was conducted. Opinions about the acceptability of IIB were asked. Based on these opinions attitude groups could be determined. Results: In total, 786 therapists completed and returned the questionnaire (response rate: 39.8%). Therapists could be divided into three attitude groups. Almost half of the therapists belonged to the 'rather restrictive group', a third to the 'rather socially permissive group' and a fifth to the 'rather sexually permissive group'. Being categorised as 'rather sexually permissive' is predominantly related to being male and non-heterosexual, whereas being 'rather restrictive' or 'rather socially permissive' is mainly due to the type of psychotherapy training. The 'rather sexually permissive' therapists more often found a client sexually attractive during the last year and fantasised more often about a romantic relationship with a client, but they did not more often started a sexual relationship. Conclusions: Most therapists in Flanders are rather restrictive in their attitude to IIB, pointing to a high sense of morality. Having a rather sexually permissive attitude is predominantly related to more personal characteristics of the therapists, but these therapists did not start a sexual relationship more often.